7)sinx + cosx = cotx - tanx
đk: sinx ≠ 0 và cosx ≠ 0 → sin2x ≠ 0 ⇔ x ≠ kπ/2 (k ∈ Z)
pt ⇔ sinx + cosx = cosx/sinx - sinx/cosx
⇔ sinx + cosx = (cos²x - sin²x)/(sinx.cosx)
⇔ sinx.cosx.(sinx + cosx) = (cosx - sinx)(cosx + sinx)
⇔ (sinx + cosx)(sinx.cosx - cosx + sinx) = 0
⇔ [ sinx + cosx = 0
[ sinx.cosx + sinx - cosx = 0
+) sinx + cosx = 0 ⇔ tanx = -1 ⇔ x = -π/4 + kπ (k ∈ Z): t.m đk
+) sinx.cosx + sinx - cosx = 0
đặt t = sinx - cosx = √2.sin(x - π/4) → -√2 ≤ t ≤ √2 (*)
→ t² = sin²x - 2sinx.cosx + cos²x
→ t² = 1 - 2sinx.cosx → sinx.cosx = (1 - t²)/2 , thay vào pt trên ta có:
(1 - t²)/2 + t = 0
⇔ t² - 2t - 1 = 0
⇔ t = 1 - √2 (t/m đk) hoặc t = 1 + √2 : loại do ko t/m đk (*)
t = 1 - √2 → √2.sin(x - π/4) = 1 - √2 ⇔ sin(x - π/4) = (√2 - 2)/2
⇔ [ x = π/4 + arcsin[(√2 - 2)/2] + k2π (k ∈ Z)
[ x = 5π/4 - arcsin[(√2 - 2)/2] + k2π (k ∈ Z) , 2 họ nghiệm này đều t/m đk ban đầu